DESIGN AND STRESS ANALYSIS OF RX-122 ROCKET MOTOR TUBE USING NUMERICAL METHOD - Wibawa, Lasinta Ari Nendra; Rusyana, Iyus; Koswara, Dinar; Nugraha, Gagan; Muhdiyat, Diyat; Irawan, Dedi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
The RX-122 rocket is an experimental rocket series developed by the Technology Centre for Rocket-BRIN. The lightweight design of the RX-122 rocket motor tube is an essential requirement for improving the rocket's flight performance. The objective of this research is to identify a rocket motor tube design that offers both safety and minimal weight. A total of 12 different design configurations for the rocket motor tube are examined using numerical methods assisted by Ansys software. Aluminium 6061-T6 material was chosen to withstand an internal operating pressure load of 10.5 MPa. The design involves examining a range of wall thickness options, including 4 and 5 mm, cap thickness options of 15 and 20 mm, and fillet radii of 10, 15, and 20 mm. This approach provides a comprehensive and systematic method to achieve optimal structural performance under operational stress conditions, ensuring that only safe yet lightweight configurations are selected. This evaluation, which integrates the exploration of wall, cap, and fillet dimensions, offers an innovative framework to optimize the balance between safety and weight. The findings indicate that only the 12th design, featuring a wall thickness, cap thickness, and fillet radius of 5, 20, and 20 mm, satisfies the specified criteria. The method demonstrates a practical advantage in refining rocket design with high efficiency and accuracy, reducing trial-and-error in experimental setups.